An increase in erythromycin resistance in methicillin-susceptible Staphylococcus aureus from blood correlates with the use of macrolide/lincosamide/streptogramin antibiotics. EARS-Net Spain (2004–2020) - El Mammery, Achraf; Ramírez de Arellano, Eva; Cañada-García, Javier E.; Cercenado, Emilia; Villar-Gómara, Laura; Casquero-García, Verónica; García-Cobos, Silvia; Lepe, José Antonio; Ruiz de Gopegui Bordes, Enrique; Calvo-Montes, Jorge; Larrosa Escartín, Nieves; Cantón, Rafael; et al. (Frontiers in Microbiology, 2023)
Objectives: To describe and analyse erythromycin resistance trends in blood isolates of Staphylococcus aureus (EARS-Net Spain, 2004-2020) and the association of these trends with the consumption of macrolide, lincosamide, and streptogramin B (MLSB) antibiotics. To assess molecular changes that could be involved in erythromycin resistance trends by whole genome analysis of representative isolates. Materials and methods: We collected antibiotic susceptibility data for all first-blood S. aureus isolates in patients from 47 Spanish hospitals according to EARS-Net criteria. MLSB antibiotic consumption was obtained from the Spanish Agency for Medicines and Medical Devices (2008−2020). We sequenced 137 representative isolates for core genome multilocus sequence typing, resistome and virulome analysis. Results: For the 36,612 invasive S. aureus isolates, methicillin resistance decreased from 26.4% in 2004 to 22.4% in 2020. Erythromycin resistance in methicillin-susceptible S. aureus (MSSA) increased from 13.6% in 2004 to 28.9% in 2020 (P < 0.001); however, it decreased from 68.7% to 61.8% (P < 0.0001) in methicillin-resistant S. aureus (MRSA). Total consumption of MLSB antibiotics increased from 2.72 defined daily doses per 1,000 inhabitants per day (DID) in 2014 to 3.24 DID in 2016. By WGS, the macrolide resistance genes detected were erm (59.8%), msrA (46%), and mphC (45.2%). The erm genes were more prevalent in MSSA (44/57, 77.2%) than in MRSA (38/80, 47.5%). Most of the erm genes identified in MSSA after 2013 differed from the predominant ermC gene (17/22, 77.3%), largely because ermT was significantly associated with MSSA after 2013 (11/29, 37.9%). All 13 ermT isolates in this study, except one, belonged to ST398 and came from 10 hospitals and six Spanish provinces. Conclusions: The significant increase in erythromycin resistance in blood MSSA correlated with the consumption of the MLSB antibiotics in Spain. These preliminary data seem support the hypothesis that the human ST398 MSSA clade with ermT-mediated resistance to erythromycin may be involved in this trend.